Konten Kreatif Youtube Sebagai Sumber Penghasilan Ditinjau dari Etika Bisnis Islam - Nur Qomariah Zulfa; Haya Zabidi; Muhammad Yulian Ma'mun (Musyarakah: Journal of Sharia Economic (MJSE), 2021)
The increasingly fierce business competition, especially at the global level, not only requires business actors to always be vigilant and creative, but also has an unfavorable impact on the environment and human benefit. This phenomenon implicates the many actions of business people tend to ignore the principles of business ethics. This study aims to discover how YouTube creative content is used as a source of income by Youtubers Community from South Kalimantan (Kal-Sel) and to find out its accordance with Islamic business ethics. The subjects in this research are South Kalimantan YouTubers whose Youtube channels have been monetized and have more than 100,000 subscribers. Data was collected through observation and documentation. Data was analysed using qualitative analysis by describing events and relating them to Islamic business ethics. The results of the study found that there are some YouTubers who ignore some principles of business ethics in Islam by posting negative content (obscenities, vulgar videos, and pranks), namely: Kahfi Official, Subur Gaming, Ones, Idang Nia and Ipul Hary. However, there are also some YouTubers who fulfill the principles of business ethics in Islam and are aware of the moral values of Islam in the content they produce, namely: Nomad Pro Story, Eybel Channel, Said Jola, AS Game, Sceror and Tommy Kaganangan.